Repeatability and reliability of kinetic and temporospatial gait parameters measured with a pressure-sensitive treadmill in healthy cats - Weißig, Dorothea M.; Dobenecker, Britta; Zablotski, Yury; Lauer, Susanne K. (Frontiers in Veterinary Science, 2025)
ObjectivesInterest in feline kinetic gait variables has increased substantially. This study aimed to assess repeatability and intersession reliability of kinetic gait analysis in healthy cats using a pressure-sensitive treadmill.MethodsHealthy client-owned cats (n = 9) and cats housed at the cattery of the Chair of Animal Nutrition and Dietetics (n = 5), without orthopedic abnormalities based on history, examination, and subjective gait analysis, were enrolled. Cats (mean body weight: 5.2 ± 0.9 kg, age: 4.1 ± 1.7 years) were acclimated to a pressure-sensitive treadmill system (FDM-T-CanidGait®, zebris Medical GmbH, Isny, Germany). Treadmill velocity was adjusted individually for comfortable walking. For data acquisition, cats were placed on the treadmill and repositioned if they jumped off (total duration: 10 min, 5 × 2 min). The first five sequences with six valid gait cycles were selected. Data acquisition was repeated after 2 weeks at the same speed. Average maximal pressure, loaded paw surface, step and stride length, step width, stance and swing phase percentages, hind reach, step-stride ratio, and symmetry indices were calculated. Repeatability was assessed with linear mixed-effects models and intersession reliability with intraclass correlation coefficients (ICCs). Reliability was categorized as excellent, good, moderate, or poor, with statistical significance set at a p-value of < 0.05.ResultsMost parameters did not differ significantly between time points, except for the average maximal pressure of the left hindlimb (p = 0.037) and hind reach of both hindlimbs (p ≤ 0.001). ICCs demonstrated good to excellent reliability (0.885–0.988) for all variables, except for symmetry indices (moderate reliability; forelimbs: 0.547, hindlimbs: 0.676).Conclusion and relevanceA pressure-sensitive treadmill provides repeatable feline gait measurements with good to excellent intersession reliability for most variables and moderate reliability for symmetry indices, offering a reference for future studies. Further studies involving larger cohorts are needed to confirm these results and support broader clinical application.